Feminine and feminist ethics - Tong, Rosemarie (Belmont, Calif. : Wadsworth Pub. Co., 1993)
Rosemarie Tong's clear, compelling voice is evident throughout this fascinating examination of feminine and feminist ethics. An ideal introduction to a controversial topic, the book makes feminist issues accessible even readers who may be put off by philosophy or feminism. This is the first single-author attempt to survey the entire spectrum of feminist ethics. Professor Tong writes in an interesting, lucid style that involves students and makes them think, yet is accessible to those who may be potentially afraid of philosophy and/or feminism. The realistic examples and clear language make this text ideal as an introduction to a difficult and controversial subject.
1. Feminine and Feminist Ethics: A First Approximation --- 2. Traditional Types of Ethical Theories: General Definitions --- 3. Women's Morality: Precursory Feminine and Feminist Approaches to Ethics --- 4. The Ontological and Epistemological Conditions for Feminine and Feminist Approaches to Ethics --- 5. Carol Gilligan's Ethics of Care --- 6. Nel Noddings's Relational Ethics --- 7. Maternal Ethics --- 8. Feminist Approaches to Ethics --- 9. Lesbian Approaches to Ethics --- 10. Conclusion.
Includes bibliographical references and index.
Keywords: Feminist ethics; Women -- Psychology; Human reproduction -- Moral and ethical aspects; Feminist ethics; Human reproduction -- Moral and ethical aspects; Women -- Psychology